2013
DOI: 10.1007/s10549-013-2766-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease among breast cancer survivors: the call for a clinical vascular health toolbox

Abstract: With better detection and treatment, breast cancer is less likely to be the primary cause of death in the majority of breast cancer survivors; mortality due to cardiovascular disease (CVD) is now more common. Given the long latency periods between cancer treatment completion and potential symptomatic CVD, there is a need to detect vascular changes before symptoms appear. This short review provides an overview of non-invasive, widely available, and relatively inexpensive techniques for assessing endothelial fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Frequently, such changes are only clinically observed months or years after the use of these medications. 2 , 8 , 12 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Frequently, such changes are only clinically observed months or years after the use of these medications. 2 , 8 , 12 …”
Section: Discussionmentioning
confidence: 99%
“…This fact may be due to the short period of patients follow-up, which does not allow the demonstration of a clinical change through this method - although structural and molecular microalterations have been shown early in this profile of patients, in the first months after treatment. 3 , 11 , 12 There are studies suggesting that most cardiovascular alterations occur in the early stage, from the third month after the end of chemotherapy. 2 , 12 Furthermore, because it is a pilot study, the reduced sampling may have contributed to this result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assessment of arterial stiffness, which increases early in the atherosclerotic process, to provide vasculotoxic profiles of chemotherapeutic agents seems to be very proimising. These could be useful in the future in improving therapeutic strategies (84,179,273,425). Drafts et al found, by magnetic resonance imaging of the aorta, an early (*3 months) and abrupt increase of pulse wave velocity, a marker of arterial stiffness, which was dose-, age-, and CV risk factor independent in patients treated with ANTs; furthermore, this increase was accompanied by a subclinical reduction in LVEF and strain (81).…”
Section: E Detection Of Vascular Complications: Old and New Strategiesmentioning
confidence: 99%
“…Dysfunction within the arterial system, including increased aortic arterial stiffness has been proposed as an early prognostic indicator for cardiac events, including in breast cancer survivors [18]. Arterial stiffness describes the compliance of the arterial vascular system [14,21] and is recognised as a surrogate end point for cardiovascular disease [43].…”
Section: Introductionmentioning
confidence: 99%